Prevalence of Congenital Malaria in Kisangani, A Stable Malaria Transmission Area in Democratic Republic of the Congo - Labama Otuli Noël; Bosenge Nguma Jean-Didier; Maindo Alongo Mike-Antoine; Katenga Bosunga Gedeon; Mbo Mukonkole Jean-Paulin; Losimba Likwela Joris; Manga Okenge Jean-Pascal (Hindawi Limited, 2020)
Background. Gestational malaria is a major public health problem. It produces fetal complications such as low birth weight, perinatal mortality, and congenital malaria. The present study is aimed at determining the prevalence of congenital malaria and its neonatal complications in the city of Kisangani. Methods. We conducted a cross-sectional study in Kisangani from 1 January to 30 September 2018. Our study population was composed of 1248 newborns born in our study sites, during the period of our study. Just after their birth, we performed the thick drop smear in the placental print and in umbilical blood smear. Results. The prevalence of congenital malaria was 13.98%; 69.23% of newborns who contracted congenital malaria were from 18- to 34-year-old mothers, 53.85% from primiparous mothers, 92.31% from mothers who took intermittent preventive treatment in pregnancy with Sulfadoxine-Pyrimethamine, all (100%) from mothers using the insecticide-treated mosquito nets and 7.69% from HIV-positive mothers. Low birth weight and perinatal mortality were recorded in 76.92% and 7.69% of congenital malaria cases, respectively. Intermittent preventive treatment in pregnancy with Sulfadoxine-Pyrimethamine had no effect on congenital malaria (FE=0.5218; OR: 0.8, 95% CI: 0.1651-3.8769) and on low birth weight (FE=0.3675; OR: 1.2308, 95% CI: 0.0037-0.1464); however, it seemed to have protective effect against perinatal mortality (FE=0.0001; OR: 0.0233, 95% CI: 0.0037-0.1464). Conclusion. Congenital malaria remains a major problem in stable malaria transmission area like Kisangani, and it is grafted by major perinatal complications, particularly low birth weight and perinatal mortality. We recommend an extended study to clarify the relationship between the outcome of pregnancy and the intermittent preventive treatment in pregnancy with Sulfadoxine-Pyrimethamine.